2007
DOI: 10.1111/j.1440-1754.2007.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in a sample of patients affected by Prader–Willi syndrome

Abstract: Physical and mental aspects of quality of life are impaired in Prader-Willi patients, weight is the clinical finding which mainly influences negatively the physical aspects of quality of life. However, weight does not cause mental problems. These are mainly due to the presence of characteristic facial features. Interestingly, a high birthweight is associated with less impairment of the mental aspects of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…In a study investigating HRQOL in 9 untreated children with PWS (age range 5-14 years) [8], HRQOL was found to be lower in children with PWS compared to a reference population. However, in that study, HRQOL was rated by parents only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating HRQOL in 9 untreated children with PWS (age range 5-14 years) [8], HRQOL was found to be lower in children with PWS compared to a reference population. However, in that study, HRQOL was rated by parents only.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed that GH treatment can improve the physical and psychological aspects of health-related quality of life (HRQOL) in adolescents and adults with PWS [7,8], but information about HRQOL or the effect of GH treatment on HRQOL in children with PWS is scarce. One study investigated HRQOL in 19 adolescents after 10 years of GH treatment and observed a lower HRQOL than in the general population on the items of mobility, breathing, speech, mental function, going to school, and getting and having friends [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tal es así, que durante las dos últimas décadas los investigadores han destacado la necesidad de evaluar la CV de los niños y niñas con ER, con el objetivo de determinar el impacto que estas enfermedades y los tratamientos tienen sobre sus vidas (Caliandro et al, 2007). Vivir con enfermedades y discapacidad puede afectar a la vida diaria en muchos aspectos.…”
unclassified
“…child psychiatrists, pediatric endocrinologists, clinical geneticists, orthopedic specialists, educational psychologists, and social workers). However, all these professional figures should know what the patient wants and what kind of relationship there is between the traditional clinical outcome measures and the patient's perspective 4) . Over the last two decades, clinical researchers have emphasized the need for a thorough evaluation of the patient's QoL in order to study the impact of chronic illnesses and their treatments on the patient's life 5) .…”
mentioning
confidence: 99%
“…There are few reports on QoL in patients with PWS. Caliandro et al reported an assessment of QoL in patients with PWS in Italy 4) . They performed a multi-center study on 40 consecutive patients with PWS evaluated through the Short Form-36 and the Child Health Questionnaire-Parent Form-50 according to the age of patients, which showed intensely impaired QoL in mental and physical aspects.…”
mentioning
confidence: 99%